PENGARUH LIFESTYLE, EFEK KOMUNITAS DAN FITUR PRODUK TERHADAP KEPUTUSAN BRAND SWITCHING SMARTPHONE BLACKBERRY KE MEREK LAIN - Deasy Purnama Sari; Wahyu Hidayat; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2014)
This research was motivated by the presence of advancement in telecommunicationtechnology that revives producers to make it as business opportunities where the competition isgetting stricter. Specifically, this study discusses about the downward trend in sales of BlackberrySmartphone in over two year period. The increase of people’s lifestyle, the influence of social groups,also other smartphones that offer more sophisticated features often lead many consumers to chooseother brand than Blackberry. The sample in this research is 100 respondents using samplingtechniques of non-probability sampling. Linear regression analysis and significance test is used totest the hypothesis using SPSS 16.0. The study results indicate that all of the independent variables,lifestyle (X1), community effects (X2), and the product features (X3) partially each have a positiveand significant effect on the dependent variable of brand switching decisions (Y).